PENDAMPINGAN MASYARAKAT DESA AIR ANYIR MELALUI PEMANFAATAN POTENSI LOKAL “LIDI NIPAH” - Darman Saputra; Dini Oktariani; Nanang Wahyudin; Christianingrum Christianingrum (Universita Bangka Belitung, 2022)
Abstract : The Merdeka Campus Competition Program (PKKM) is a form of Merdeka Campus acceleration to encourage higher education transformation and innovation on the basis of study programs so that learning is 4.0. There are many problems and obstacles for MSMEs in developing to compete and differentiate products sold from products from outside Bangka Belitung. Therefore, it is necessary to carry out Community Service (PKM) activities to overcome this. PKM activities have been carried out to the COMMUNITIES of Air Anyir Village, Bangka Regency. Business Motivation Socialization Training The theme of this outreach is